Representasi Kritik Sosial dalam Animasi Tekotok Edisi Maret-Agustus 2021 - Izzah Afgarina, Nuril (Meyarsa: Jurnal Ilmu Komunikasi dan Dakwah, 2023)
This research focuses on the social criticism contained in the March-August 2021 Edition of Tekotok Animation by taking five episodes in it. The formulation of the problem in this study is how to represent social criticism contained in the March-August 2021 Edition of the Tekotok animation with the aim of identifying and knowing the full meaning that shows social criticism in predetermined episodes. Using a qualitative method with Ferdinand De Saussure’s semiotic analysis as the analytical knife. The results of this study provide a conclusion that animation is also able to represent something around it. The social criticism resulting from this animation refers to several cases of legal inequality and violations of norms in society. This broadcast serves as a reminder in the form of criticism and satire which is neatly packaged so that people are able to accept it well, not forced and as it is.